Evaluation of post-education and training to determine alumni performance quality - Nia Kurniawati (Curricula: Journal of Curriculum Development, 2023)
Education and training are structured and planned actions or processes with the aim of forming an optimal learning environment. The purpose of this article is to increase understanding of post-education and training evaluation and the importance of seeing the quality of education and training alumni on an ongoing basis. Through an effective and continuous evaluation, we can identify the strengths and weaknesses of training programs, provide recommendations for appropriate improvements, and improve the quality of education and training alumni to face competition in the ever-evolving world of work. The method used in this research is a descriptive method using a literature study approach. The findings obtained from this article are that as a whole, the community has not directly experienced the impacts and benefits provided by the various types of training held. The conclusion is that it is often found that a training activity is ultimately only limited to measuring the output of training participants and tends to ignore alumni outcomes. Outcomes of this training can be known through post-training evaluation activities which are carried out three to 6 months after the training is completed.